2015
DOI: 10.1515/tjj-2014-0032
|View full text |Cite
|
Sign up to set email alerts
|

Tab Aspect Ratio Effect on Supersonic Jet Mixing

Abstract: The efficacy of introducing mixing promoting small-scale vortices by two rectangular tabs, of aspect ratio 1.0, 1.5 and 2.0, placed at diametrically opposite locations at the exit of a Mach 1.73 convergent–divergent circular nozzle has been experimentally investigated, for NPRs from 4 to 8, covering overexpanded, correctly expanded and underexpanded states of the jet. The area blockage due to the each tab was 2.5% of the nozzle exit area. Keeping the blockage constant, the aspect ratio (defined as the ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Based on the formula, Blockage ratio = Nozzle exit area/Probe area, the blockage ratio as a result of the probe's presence was calculated to be 1111.11. The tolerable probe blockage value of 64 established by Kaushik (2012) is very mush lesser than this value; therefore the probe blockage doesn't radically affect the pressure reading. Also, since the Reynolds number for the jet Mach numbers considered in this investigation are comparatively greater than 500, the effects of viscosity are deemed negligible on the pressure measurements.…”
Section: Pitot Probementioning
confidence: 92%
“…Based on the formula, Blockage ratio = Nozzle exit area/Probe area, the blockage ratio as a result of the probe's presence was calculated to be 1111.11. The tolerable probe blockage value of 64 established by Kaushik (2012) is very mush lesser than this value; therefore the probe blockage doesn't radically affect the pressure reading. Also, since the Reynolds number for the jet Mach numbers considered in this investigation are comparatively greater than 500, the effects of viscosity are deemed negligible on the pressure measurements.…”
Section: Pitot Probementioning
confidence: 92%
“…Kaushik and Rathakrishnan [34] experimentally investigated the tab aspect ratio effect on mixing, promoting effectiveness at Mach 1.73 nozzle. They have used three different plain rectangular tabs with aspect ratios of 1.0, 1.5, and 2.0, placed diametrically opposite positions at the nozzle outlet.…”
Section: Supersonic Jet Controlled With Tabsmentioning
confidence: 99%
“…Delta-tabs were used and it was found that two delta-tabs, spaced 180 • apart, absolutely dichotomized the jet. Kaushik andRathakrishnan (2013, 2015) clearly revealed that the magnitude and potency of vortices actuated from control tabs can be enhanced with geometrical alterations [8,9]. A recent work by Thillaikumar et al (2020) suggested that the introduction of vortex actuating tabs in the divergent section of the supersonic nozzle changes the structure of the shock cell, thereby reducing the jet core length [10].…”
Section: Introductionmentioning
confidence: 99%